Hadith #3068 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Hafs bin Sulaiman al-Asadi حفص بن سليمان الأسدي; Kathir bin Zadhan al-Nkh'y كثير بن زاذان النخعي الكوفي (Jami' al-Tirmidhi)
“I was reclining in the presence of ‘Aishah when she said: ‘O Abu ‘Aishah! There are three things, whoever speaks of one of them, then he has uttered one of the worst lies against Allah. Whoever claims that Muhammad saw his Lord. Then he has uttered one the worst lies against Allah, Allah says: No vision can grasp Him, but His grasp is over all vision, and He is the Most Subtle, Well-Acquainted with all things (6:103). It is not for any human being that Allah should speak to him unless (
Grade:

Hadith #221 - Sunan Ibn Majah - Ali ibn Abi Talib; Amr bin 'Uthman عمرو بن عثمان بن عفان; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Kathir bin Zadhan al-Nkh'y كثير بن زاذان النخعي الكوفي; Muhammad bin Harb al-Wasti محمد بن حرب بن حرمان النشائي (Sunan Ibn Majah)
“May my ears be made deaf, if I did not hear the messenger of Allah saying: ‘Perform ablution after (eating) that which has been changed by fire.'”
Grade: